Systematization of Nursing Care for the Elderly in Primary Health Care: An Integrative Literature Review - , Kélia das Graças de Paiva Macias Nakai, Rebecca Máxima de Souza Lopes, Thais Garcia Raymond Franco, Paula Carolina Lima de Aviz, Letícia Dias Pena, Carla Daniara Feitosa Coelho, Bruno da Silva Mendonça, Danielle de Alencar Alves dos Santos Franco, Darlete Godinho da Veiga, Elem Gabriela Reis Pinheiro, Annely Barros Góis, Eneida Horta Costa; et al. (Archives of Current Research International, 2025)
Background: The global increase in life expectancy has intensified the demand for qualified health services aimed at the elderly, particularly within Primary Health Care (PHC). In this context, the Systematization of Nursing Care (SNC) emerges as a fundamental strategy to guide professional practice, ensuring comprehensive, individualized, and continuous care. SNC enables structured nursing actions through standardized methodologies, contributing to the promotion, prevention, and management of health conditions in older adults. Despite its recognized importance, challenges in its application persist, especially in PHC settings, where resource limitations and professional training gaps can hinder its full implementation. Objective: This study aimed to analyze the evidence available in the literature on the Systematization of Nursing Care (SNC) aimed at caring for the elderly in Primary Health Care (PHC). Methods: This is an integrative bibliographic review, with a qualitative approach, carried out between March and April 2025, with searches in the SciELO, LILACS, BDENF and PubMed databases, using descriptors such as “elderly”, “primary health care” and “systematization of nursing care”. Were included 14 articles published between 2019 and 2024, in Portuguese, English or Spanish. Results: The results were organized into three categories: (1) systematized approaches in nursing consultations for the elderly, highlighting the importance of multidimensional assessment and the construction of a care plan; (2) instruments and technologies applied to SNC, such as the use of Electronic Medical Records, CIPE® and mobile applications, which promote standardization and continuity of care; and (3) challenges faced in implementing SNC, such as work overload, lack of specific protocols and deficiencies in professional training. Conclusion: It is concluded that SNC is an essential strategy to qualify care for the elderly in PHC, but its effective implementation still depends on investments in training, infrastructure and valorization of the nursing process. Strengthening these practices is essential for the construction of comprehensive, effective and humanized care, especially in view of the aging population.